Re‐making spaces of conversion: deconstructing discourses of e‐waste recycling in China. Issue 1 (31st October 2014) - Tong, Xin; Li, Jingyan; Tao, Dongyan; Cai, Yifan
<x xml:space="preserve">Abstract</x> China implemented its e‐waste policy in 2012, declaring adherence to the principle of Extended Producer Responsibility. Public planning, policies and demonstration projects for recycling facilities have been promoted widely at city and provincial levels to rebuild the image of e‐waste management in China. This article traces the evolution of e‐waste recycling practices in China, from imported e‐waste recycling clusters in coastal rural areas and e‐waste disassembly and trading bazaars in suburban areas of big cities to certified e‐waste recyclers subsidised by the government, as well as the waste reduction and recycling efforts of electronics producers. We draw out the logic underpinning the planning of large‐scale collection and sorting centres – armed with automated equipment – to replace the labour‐intensive sorting activities prevalent in the waste villages. By deconstructing and analysing the discourses of e‐waste recycling, which discriminate recycling practices into formal and informal categories, we point out the limits of formalisation, which favours short and standard shredding for material recovery instead of reuse.